THE ROLE OF SAMANERA EDUCATION MANAGEMENT IN STAB KERTARAJASA BATU EAST JAVA - I Ketut Damana (Jurnal Ilmiah Kampus: Sati Sampajanna, 2019)
The problem raised in this study was the education of samanera at STAB Kertarajasa. Thisstudy was aimed to describe the role of management of samanera education at STAB KertarajasaBatu, East Java. This research used descriptive qualitative research. The informants in this study werethe chairman, lecturer, and administration staff of STAB Kertarajasa Batu, East Java. The data werecollected by using interview, observation, and documentation method. The data were analyzed byusing the Miles Huberman model which consists of data collection, data reduction, display data,and verification. The results of this research were focused on (a) management of luhur samanerabehavior at STAB Kertarajasa, (b) samanera's simple life forms program at STAB Kertarajasa (c)factors affecting hard training on samanera education at STAB Kertarajasa. (d) obstacles tomanaging samanera education at STAB Kertarajas, (e) samanera's response in the community.